European Microscopy Congress 2016: Proceedings 2016
DOI: 10.1002/9783527808465.emc2016.4672
|View full text |Cite
|
Sign up to set email alerts
|

Formation of bimetallic clusters in superfluid helium nanodroplets analysed by atomic resolution electron tomography

Abstract: Structure, shape and composition are the basic parameters responsible for properties of nanoscale materials, distinguishing them from their bulk counterparts. To reveal these in three dimensions at the nanoscale, electron tomography is a powerful tool. Advancing electron tomography to atomic resolution in an aberration-corrected transmission electron microscope remains challenging and has been demonstrated only a few times using strong constraints or extensive filtering. Here we demonstrate atomic resolution e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…Unexpectedly, the Au NPs remained stable up to 473 K, which was remarkably different from the published studies describing Au NP sintering during the CO oxidation reaction 14 conducted in 300-410 K temperature range. This 15 whereas other deposition studies have demonstrated soft landing 8b, 12 . Calculations by deLara-Castells 16 indicated that an Au atom in a small He droplet landing on TiO2 is indeed a soft landing process.…”
Section: Toc Graphicsmentioning
confidence: 74%
“…Unexpectedly, the Au NPs remained stable up to 473 K, which was remarkably different from the published studies describing Au NP sintering during the CO oxidation reaction 14 conducted in 300-410 K temperature range. This 15 whereas other deposition studies have demonstrated soft landing 8b, 12 . Calculations by deLara-Castells 16 indicated that an Au atom in a small He droplet landing on TiO2 is indeed a soft landing process.…”
Section: Toc Graphicsmentioning
confidence: 74%
“…The contribution of the droplets' superfluid character to the observed energy modulation cannot be deduced from the present results and remains to be investigated, for example with non-superfluid 3 He droplets or mixed 3 He/ 4 He droplets 43 . It will also be important to investigate the ratio of light-induced energy gain and energy dissipation in other materials, like molecular, metal or semiconductor clusters, the creation of which is facilitated by the very flexible opportunities provided by the He droplet approach for the creation of tailor-made bi-material core-shell nanostructures within the droplet 44,45 . Photoionization of the core will allow to observe LAESacceleration and energy dissipation within the shell material.…”
Section: Discussionmentioning
confidence: 99%
“…The calculated parameters are used to correct all SI data. 57 Alignment of the tilt series is done using the HAADF STEM data. For alignment in the direction of the tilt axis, common-line alignment is applied, 58 in the direction perpendicular to the tilt axis the center of mass of each projection is used for alignment and for tilt axis alignment, rotational centers are calculated based on the center of mass.…”
Section: Data Preprocessingmentioning
confidence: 99%